(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
China’s economic progress is dependent on energy security and sustainability. The establishment of a theoretical energy evaluation system is of theoretical and practical importance for guaranteeing the safe and sustainable development of energy security commensurate with the national development phase and reflective of the sustainable development of national energy. Sustainable energy security must not only take into account the security of energy supply–demand in the long-term and short-term, it must also focus on the coordinated development between energy and the Geopolitical Dimensions in China. This paper proposes Geopolitical Dimensions of Energy in China, based on the model, an empirical study of China’s energy security is carried out with data from 2005 to 2015, and dynamic changing trends are analyzed accordingly. The results indicate that availability and develop-ability of Energy in China. China bears a hefty tax on the increase in global oil prices, since global demand is rising and reserve production capacity is falling, and it feels extremely vulnerable as a result of the continued betting on oil prices. The search for abroad energy supplies conducted by China’s main energy companies as part of China’s strategy has not produced as many successes as had been anticipated. Chinese companies have also acquired stakes in energy-related projects in Canada and Australia, and actions have prompted China to take a number of steps to strengthen its relations with oil-producing nations, including Russia, Canada, the Arabian Gulf, and others. China has ambitious aspirations to increase its nuclear power production, and its strategic goals are centred on increasing its nuclear power output capacity to 60 gigawatts by 2020. In order to conserve the environment and combat global warming, technological advancements in alternative energy investment are essential.